FRI0169 Elevated LBP Levels and in Vivo Activation of Monocytes as Potential Indicators of Bacterial Translocation in Axial Spondyloarthritis. (10th June 2014) - Conrad, K.; Wu, P.; Poddubnyy, D.; Sieper, J.; Syrbe, U.
Abstract : Background: Subclinical gut inflammation is often present in axSpA patients [1, 2]. This may result in enhanced translocation of mucosal antigens leading to activation of monocytes which are very sensitive sensors of bacterial antigens. Objectives: Here we determined lipopolysaccharide binding protein (LBP) serum levels as a potential marker of bacterial translocation and evaluated monocyte function and activation in axSpA patients treated either by standard therapy, i.e. NSAIDs, or by TNF inhibitor (TNFi) therapy which has mucosal healing property. Methods: LBP was determined in the serum of axSpA patients under standard treatment from the GESPIC cohort and in axSpA patients before and after 12 weeks of TNFi treatment. Whole blood of axSpA patients (n=26) and healthy controls (n=21) was stimulated without or with different TLR-ligands (LPS, FSL, PAM3 CSK4 ) and the NOD-2-ligand muramyldipeptide (MDP) for 5 hours. Brefeldin A was added for the last 3 hours. Cytokines (IL-1b, IL-6, TNFa, IL-1RA) were stained intracellularly and detected by FACS among CD68+ monocytes. TLR4 expression was determined by FACS. Results: Serum levels of LPB were significantly elevated in axSpA patients under standard treatment (axSpA 41.7±2 μg/ml, Co: 19.2±3.6 μg/ml; p<0.001). In patients starting TNFi treatment LBP levels normalized after 12 weeks of treatment. In whole blood stimulations we found significantly higher frequencies of monocytes producing IL-1b, IL-6, and TNFa spontaneously or in response to MDP in axSpA patients with standard treatment compared to controls. In contrast, LPS-induced monocytic cytokine production was reduced in these patients compared to healthy controls (IL-1b and TNFa p<0.01, IL-6 p<0.05; Table I: exemplary data for IL-1b). In axSpA patients under TNFi treatment no such disturbed monocytic cytokine response was found. Responses to FSL and PAM3 CSK4 were similar in axSpA patients and controls. No difference in expression of the LPS receptor TLR4 on monocytes was found between axSpA patients and controls. Conclusions: The elevated LPB levels in axSpA patients under standard treatment suggest increased bacterial translocation which promotes monocyte activation indicated by enhanced spontaneous and MDP-induced cytokine production in these patients. The reduced LPS response can be directly related to elevated LPB levels which can quench LPS responses. Normalization of LBP and monocytic responses under TNFi treatment may be related to the mucosal healing property of TNFi. References: Mielants H, Veys EM, Cuvelier C, De Vos M, Goemaere S, De Clercq L, Schatteman L, Elewaut D: The evolution of spondyloarthropathies in relation to gut histology. II. Histological aspects. The Journal of rheumatology 1995, 22(12):2273-2278. Van Praet L, Van den Bosch FE, Jacques P, Carron P, Jans L, Colman R, Glorieus E, Peeters H, Mielants H, De Vos M et al: Microscopic gut inflammation in axial spondyloarthritis: a multiparametric predictive model. Annals of the rheumatic diseases 2013, 72(3):414-417. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4748